Detection of former goaf and analysis of deformation characteristics of overburden in Dameidong coal mine - Wei, Zhan-Xi; Zhao, Meng; Xie, Fei-Hong; Cao, Sheng-Hong; Dong, Jian-Hui; Dong, Yang-Dan (Frontiers in Earth Science, 2023)
In order to analyze the deformation of the old goaf in Dameidong Coal Mine and its influence on the surrounding rock and soil layer, it provides guidance for the prevention and control of geological disasters in the region. In this paper, the transient electromagnetic method and numerical simulation method were used to study the deformation law of the overlying strata in the mining area. The results of transient electromagnetic detection showed that the subsidence area of the goaf in Dameidong Coal Mine was within the range of the elliptical water-rich area, and the average buried depth of the goaf was expected to be 90 m. The model was established by discrete element numerical simulation to study the variation law of mining overburden rock. The results showed that the stress change in coal mining was mainly reflected at both ends of the goaf, which was a stress concentration phenomenon. Overburden rock deformation changed with the mining process. The stress concentration area and the displacement change area were highly coincident, consisted with the displacement monitoring map, showing a “U”-type distribution. The results proved that the numerical simulation results do have theoretical guidance for mining subsidence control.